2007
DOI: 10.1590/s0104-42302007000600015
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre o estresse do cuidador e as características clínicas do paciente portador de demência

Abstract: Artigo recebido: 24/01/06 Aceito para publicação: 25/09/07 CONCLUSION. Burden was associated with behavioral disorders, dependencies, cognitive impairment, and onset of symptoms, caregiving and co-residency. Black caregivers demonstrated lower levels of stress. [Rev Assoc Med Bras 2007; 53(6): 497-501]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
18
1
46

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 11 publications
12
18
1
46
Order By: Relevance
“…The average value on the Zarit scale was 32 points. 39 Babarro et al (2004) demonstrated a high level of burden among the caregivers of elderly individuals with dementia in Spain, with a similar sociodemographic profile to that observed in our study, with a burden on 72.3% of the sample (55.5% at a high level). 34 It should be emphasized that a high level of burden on the caregiver increases the risk of depression and raises the self-reported impression of poor quality of life.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The average value on the Zarit scale was 32 points. 39 Babarro et al (2004) demonstrated a high level of burden among the caregivers of elderly individuals with dementia in Spain, with a similar sociodemographic profile to that observed in our study, with a burden on 72.3% of the sample (55.5% at a high level). 34 It should be emphasized that a high level of burden on the caregiver increases the risk of depression and raises the self-reported impression of poor quality of life.…”
Section: Discussionsupporting
confidence: 88%
“…However, in the light of the available knowledge it is not possible to state what could be considered a high burden based on the Brazilian Portuguese version of the Zarit scale, although it is possible to use the scale for comparison. 14 A similar result to ours was reported by Cassis et al (2007), who assessed 67 elderly individuals with dementia, whose caregivers were mostly female and with formal education for 9.2 years. The average value on the Zarit scale was 32 points.…”
Section: Discussionsupporting
confidence: 87%
“…Other factors that are also strongly associated with higher levels of stress among caregivers are the severity of functional loss and the extent of cognitive impairment (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Brazilian studies of the burden that Alzheimer disease patients place on caregivers have mostly been carried out in the Southeast region of the country, and they point out co-residence, time spent caring for the patient, and type of relationship with the patient as important factors associated with the burden 6,11,12 . However, such studies deal with mental diseases from different etiologies, with a small number of samples.…”
Section: Introductionmentioning
confidence: 99%